Does Private Sector Participation Improve Performance in Electricity and Water Distribution? - Gassner, Katharina; Popov, Alexander; Pushak, Nataliya (Washington, DC : World Bank, 2012)
This study addresses the question with a rigorous econometric approach and distills global results from a multitude of evidence. The data set compiled is unique in its coverage, size, and composition, making it possible to address for the first time methodological problems that have plagued empirical research and hampered conclusive results. The findings provide some answers, but also indicate where the challenges lie going forward. Privately run water and electricity utilities outperform comparable state-owned companies in terms of labor productivity and operational efficiency, but staff reductions also occur. Policy makers need to be aware of and acknowledge both the benefits and the costs of reform. Clear communication between stakeholders plays an important role in the acceptance and success of private participation, and a strategy for mitigating labor issues should be an integral part of reform efforts. The study also makes it clear that the investment problem is not solved by private participation alone, and it raises questions about the scope for increasing residential tariffs in low-income countries and thus the long-term sustainability of improvements in service delivery, be it by public or private operators.